Admiration in Place of Imitation: Four Medallions by Gustaw Herling-Grudziński - Śniedziewska, Magdalena (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The medallions devoted to Caravaggio, Rembrandt, Vermeer, and Ribera are a major collection of texts within Gustaw Herling-Grudziński’s entire output. Through them, he proved that he was able to write a moving text about painting while avoiding both the academic tone and flaunting his knowledge, as well as the dangers of ekphrasis transforming too often into irksome detailed inventories of the elements of a painter’s presentation. The decision to refer to these texts as medallions was equally a genological concept and a clever hedge, and a starting point for a discussion on the ambiguity of the very notion of a medallion. Herling-Grudziński would not have been himself if he had abandoned autobiographical reflections. When considering artists and their works ‘from aside’, he multiplied assumptions, proposed apocryphal versions of some biographical threads, and formulated bold unverifiable hypotheses – this was because he sided with a literary story, not an academic discourse.